La gestion en commun des ressources naturelles : une perspective critique - Jérôme Ballet (Développement Durable et Territoires)
Community-based management of natural resources is now a main figure of natural resources management. It seems to have a growing number of adherents. Its virtues are meanwhile disputable. This paper proposes a critical insight. Grounds of this approach need a more serious discussion. The application without precaution could provoke negative effects for resources as well as for population.